Audience Commodification in the Digital Era: A Study of Audience Labour on YouTube Platform - WIDYANTY, RESTY (Berumpun: International Journal of Social, Politics, and Humanities, 2025)
Social media has changed the way users interact with content, from passive to active content production and promotion. This paper explores YouTube as a platform that illustrates how digital work is performed through user involvement in consuming, creating, and sharing content. Through the application of desk research as well as Eran Fisher's framework for audience labor, the study unveils the way in which YouTube takes advantage of users as voluntary digital laborers. Findings indicate that YouTube takes advantage of users' behavior to generate economic value, typically without the users' knowledge of having a commodified function. This study contributes to a greater understanding of labor relations in the digital economy.